The Hydration and Compressive Strength of Cement Mortar Prepared by Calcium Acetate Solution - Ke Cao; Liang Wang; Ying Xu; Wenfeng Shen; Hao Wang (Advances in Civil Engineering)
Calcium acetate is the major component of the waste solution produced in treating recycled concrete aggregate (RCA) with acetic acid. Thus, the current work aims to explore the influence of calcium acetate solution on the performance of ordinary Portland cement. For this purpose, cement pastes and mortars were prepared using different concentrations, namely, 1, 2, and 3%, of calcium acetate solution. The heat evolution results confirmed that the calcium acetate solution at a concentration of 2% could accelerate the hydration of the cement. The XRD/TGA results and SEM images also indicated that more ettringite and calcium hydroxide (CH) are produced in the mortars prepared by the 2% calcium acetate solution. Moreover, the mortar containing the 2% calcium acetate solution has a denser microstructure than the control group according to the MIP tests results, and mortars cured for 3 and 28 days have a respective compressive strength, 23.34 and 15.43%, higher than the control group. The finding of this research could also contribute to studying the effect of adding metal ions to weakly acidic solutions as mixing liquids on the performance of cementitious materials.